2016
DOI: 10.1186/s40064-016-2015-x
|View full text |Cite
|
Sign up to set email alerts
|

Food intake and gestational weight gain in Swedish women

Abstract: BackgroundThe objective of this study was to investigate if food intake (dairy, snacks, caloric beverages, bread, cheese, margarine/butter, potato/rice/pasta/grains, red meat, fish and fruit/berries/vegetables) is associated with gestational weight gain (GWG) in Swedish women.MethodsFour day food records from 95 pregnant Swedish women were collected in the last trimester. GWG was calculated as weighed body weight in the last trimester (median gestational week 36) minus self-reported pre-pregnancy body weight. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 17 publications
0
21
0
1
Order By: Relevance
“…While one study demonstrated that women who consumed at least three servings of fruits and vegetables per day presented less weight gain, 27 another study found no relationship between vegetable and fruit consumption and GWG. 28 The majority of our sample reported not eating beans every day. This result is in agreement with the last Household Budget Survey that indicated the decreased consumption of foods considered healthy and popular in Brazilian culture, such as beans, fruits, and vegetables.…”
Section: Discussionmentioning
confidence: 83%
“…While one study demonstrated that women who consumed at least three servings of fruits and vegetables per day presented less weight gain, 27 another study found no relationship between vegetable and fruit consumption and GWG. 28 The majority of our sample reported not eating beans every day. This result is in agreement with the last Household Budget Survey that indicated the decreased consumption of foods considered healthy and popular in Brazilian culture, such as beans, fruits, and vegetables.…”
Section: Discussionmentioning
confidence: 83%
“…Unambiguous scores related to the abovementioned associations may have occurred because dietary patterns vary according to age, ethnicity, culture, and other lifestyle factors. In a study conducted among Swedish women, their intakes of caloric beverages, snacks, fish, and bread were positively related to excessive GWG [ 30 ]. Uusatilo et al found that greater adherence to a ‘fast food’ DP, characterized by high intakes of fast food items such as hamburgers and pizza, as well as sweets, soft drinks and added sugar, was positively associated with GWG [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Being underweight pre-pregnancy was significantly correlated with gaining too little weight compared to gaining weight within the guidelines. It is commonly emphasized that being underweight results in a higher risk of insufficient GWG, whereas being overweight and/or obese at the time of conception is related to a higher risk of excessive gain [ 1 , 6 , 27 , 30 ]. Fontaine et al showed that 33 to 50% of healthy weight women and 50 to 75% of overweight and obese women had excessive GWG [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neither of the previous studies have investigated associations between diet and GWG. We have previously shown, in a study of well-educated women, that higher intake of caloric beverages, snacks, fish and bread during pregnancy is associated with higher GWG [18]. To our knowledge, there are no population-based data published on dietary quality and GWG in Sweden.…”
Section: Introductionmentioning
confidence: 94%